Innovative Resource-Saving Equipment for Safflower Processing to Improve Oil Quality - Maigul Mursalykova; Gulnara Kokayeva; Mukhtarbek Kakimov; Bożena Gajdzik; Radosław Wolniak; Damian Dzienniak; Michał Bembenek (Foods)
This study presents an innovative, resource-efficient apparatus for safflower oil production, designed for small- and medium-sized enterprises. The developed equipment integrates grinding and pressing into a single operation, optimizing extraction efficiency while reducing operational costs and processing time. A comparative analysis of the physicochemical and fatty acid profiles of safflower oil produced using traditional and combined grinding-pressing methods confirmed the superiority of the new approach. Optimal process parameters were identified: pressing time (τ = 3.41 min) and degree of grinding (i = 0.25), which resulted in higher oil yield and improved product quality. Multiple regression and sensitivity analyses revealed that temperature is the most significant factor positively influencing oil yield, whereas excessive grinding intensity and pressure negatively impact extraction efficiency. The results of the multiple regression analysis demonstrated that pressing time had a statistically significant impact on oil yield (p < 0.05). Although temperature was identified as the most influential factor overall, the significance of pressing time indicates that this variable also contributes meaningfully to the extraction efficiency. The regression model revealed a nonlinear (quadratic) relationship between pressing time and oil yield, suggesting that there is an optimal pressing duration. Beyond this optimal point, further increases in pressing time may result in a decline in yield due to over-compression or the release of undesired compounds. Interestingly, pressing time was found to have no significant effect on oil yield, suggesting that optimizing temperature and pressure is more critical for enhancing efficiency. The developed apparatus not only enhances oil quality, particularly its fatty acid composition, but also offers a scalable, sustainable solution for improving safflower oil production. These findings highlight the feasibility of integrating grinding and pressing, paving the way for advancements in cost-effective, high-yield oil extraction technologies.